3.3 kV 4H-SiC Trench Semi-Superjunction Schottky Diode With Improved ON-State Resistance - Melnyk, Kyrylo; Renz, Arne Benjamin; Cao, Qinze; Gammon, Peter Michael; Lophitis, Neophytos; Maresca, Luca; Irace, Andrea; Nistor, Iulian; Rahimo, Munaf; Antoniou, Marina (My University, 2024)
This study describes the design and optimization of a 3.3 kV silicon carbide (SiC) semi-superjunction (semi-SJ) Schottky barrier diode (SBD). The proposed structure features a 7 μ m deep trench filled with silicon dioxide (SiO2). Aluminum (Al+) sidewall implants are carried out, which help to form a charge balance region. The on-state improvement of the proposed semi-SJ structure is 16.2%, compared to a planar diode. This results in a specific on-state resistance ( RON,SP ) of 6.2 m Ω⋅ cm2 , which surpasses the unipolar limit. The article also addresses the issue of poor blocking voltage performance associated with conventional termination techniques. To mitigate this problem, novel termination designs, which incorporate double-zone junction termination extension (DJTE) and optimally placed rings, are proposed and verified through technology computer-aided design (TCAD) simulations. The most promising structure allows, for the first time, for both a wide implantation window and a high breakdown voltage, reaching 98.3% (4365 V) of the ideal active cell breakdown.
Keywords: Schottky diodes; Doping; Silicon carbide; Silicon; Performance evaluation; Junctions; Schottky barriers